2003
DOI: 10.1080/09553000310001626126
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and dose‐dependent changes of intracellular cytokine and cytokine receptor profile of Ewing tumour subpopulations under the influence of ionizing radiation

Abstract: The observed radiation-induced changes of cytokine and receptor profile are an indication for complex intercellular interactions in view of radioresistance-associated mechanisms between cell populations within one individual tumour. The observed heterogeneous response on radiation might have therapeutic implications for an individualized therapy based on combined radiation and cytokine modulation, defined by flow cytometric characterization of markers potentially informative for radioresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…45 More recently, IR induced time-and dose-dependent increase in the expression of intracellular IL-1α was demonstrated. 46 Consistently, a number of studies identified the key role of IL-1α in induced radioprotection. 47 IL-1α has been demonstrated to stimulate NFκB activation through 1R-AcP that recruit IRAK1, 2/Traf6/MyD88 complex and activate NIK which in turn activate IKK1.…”
Section: Discussionmentioning
confidence: 80%
“…45 More recently, IR induced time-and dose-dependent increase in the expression of intracellular IL-1α was demonstrated. 46 Consistently, a number of studies identified the key role of IL-1α in induced radioprotection. 47 IL-1α has been demonstrated to stimulate NFκB activation through 1R-AcP that recruit IRAK1, 2/Traf6/MyD88 complex and activate NIK which in turn activate IKK1.…”
Section: Discussionmentioning
confidence: 80%
“…Известно также, что хроническое облучение оказывает модифицирующее влияние на состояние иммунитета, однако роль модифицирующего влияния облучения на состояние про-и антиатерогенных факторов иммунитета изучена недостаточно. Известно, что профиль экспрессии цитокинов у лиц, подвергшихся хроническому облучению, носит в основном провоспалительный характер [18,25]. Данные о содержании цитотоксических Т-лимфоцитов (CD8 + ) противоречивы.…”
Section: проатерогенные факторы иммунитетаunclassified
“…X-rays and c-rays are reported to increase the expression of integrin and interleukin, though the effect of proton irradiation is largely unknown [15][16][17][18][19][20][21]. The detection has been carried out by immunocytochemical staining and was analysed by laser scanning microscopy afterwards.…”
Section: Heat Shock Protein 70mentioning
confidence: 99%